National lung cancer screening program feasibility study in Estonia - Kallavus, Kadi; Laisaar, Kaja-Triin; Rätsep, Anneli; Kiudma, Tarvo; Takker, Urmas; Poola, Anneli; Makke, Vahur; Frik, Marianna; Viiklepp, Piret; Taur, Merily; Laisaar, Tanel (Interdisciplinary cardiovascular and thoracic surgery, 2023)
Abstract OBJECTIVES The main aim of the lung cancer screening (LCS) feasibility study was to investigate the plausibility of and bottlenecks to systematic enrolment in family physician practices by evaluating all their patients. METHODS In 3 family physician practices, for each individual born in 1947–1966 (target age group 55–74 years), information on ever smoking was gathered by a family physician/nurse. All current and ex-smokers were invited to an ‘LCS visit’. In parallel, 2 inclusion criteria were used: (1) current smoker (≥20 pack-years) or ex-smoker (quit <15 years ago and smoking history ≥20 pack-years) and (2) PLCOm2012noRace risk score >1.5. All individuals with elevated lung cancer risk were assigned low-dose computed tomography. RESULTS Among the total 7035 individuals in the 3 family physician practices, the LCS target age group comprised 1208 individuals, including 649 (46.3–57.1%) males and 559 (42.9–53.7%) females. Of the 1208 applicable age group individuals, 395 (all current or ex-smokers) were invited to the ‘LCS visit’. According to either 1 or both the LCS inclusion criteria, 206 individuals were referred to low-dose computed tomography, and 201 (97.6% of those referred) ended up taking it. The estimated participation rate in LCS, based on data from our feasibility study, would have been 87.4%. CONCLUSIONS In LCS, systematic enrolment of individuals by family physicians results in high uptake, and thus, effectiveness of the LCS in the setting of a well-functioning family physician system like in Estonia. Also, the feasibility study provided excellent input to the currently ongoing regional LCS pilot study in Estonia. Lung cancer screening (LCS), using low-dose computed tomography (LDCT), has been proved to reduce mortality in 2 large, randomized controlled studies: National Lung Cancer Screening Trial (NLST) in the USA and Dutch-Belgian Randomized Lung Cancer Screening Trial (Dutch acronym: NELSON) in Europe [1, 2].